How field office leaders drive learning and creativity in humanitarian aid: Exploring the role of boundary‐spanning leadership for expatriate and local aid worker collaboration. (28th November 2017) - Salem, Mojtaba; Van Quaquebeke, Niels; Besiou, Maria
Summary: Many humanitarian aid workers receive training prior to being dispatched into the field, but they often encounter challenges that require additional learning and creativity. Consequently, aid organizations formally support collaboration among the expatriate and local workers in a field office. At best, those aid workers would not only exploit their joint knowledge but also explore novel ways of managing the challenges at hand. Yet differences between expatriate and local groups (e.g., in ethnicity, religion, education, and salary) often thwart intergroup collaboration in field offices and, by extension, any joint learning or creativity. In response to this issue, we study the role of field office leaders—specifically, how their boundary‐spanning behavior may inspire collaboration between the two groups and therefore facilitate joint learning and creativity. We propose that a leader's in‐group prototypicality additionally catalyzes this process—that is, a leader's behavior has more impact if s/he is seen as representing his/her group. We tested and found support for our hypothesized moderated mediation model in a field sample of 137 aid workers from 59 humanitarian organizations. Thus, our study generally highlights the pivotal role that field office leaders play for crucial outcomes in humanitarian aid operations. Furthermore, we offer concrete steps for field office leaders who want to inspire better collaboration between the expatriate and local aid workers they lead.